Fermenting for fertility - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
One way to maintain soil fertility when growing perennial crops is to apply liquid manure as a top dressing. You can mix animal dung with water and leave it to ferment, but if fresh water is scarce the following easy method from Sarah Kimaakwa of...